2nd International Congress on Energy Efficiency and Energy Related Materials (ENEFM2014) Proceedings, Oludeniz, Fethiye/Mugla, Turkey, October 16-19, 2014 - Ducrotoy, Jean-Paul; Elliott, Mike (Springer Proceedings in Energy, 2015)
XXIX, 605 p. 299 illus., 205 illus. in color.